Analysis of Local Culture in Primary School Education Curriculum in Banggai District - Salingkat, Suhartini; Lajiba, Saipul Bachri S.; Ahmadin, Ahmadin; Wibowo, Edy (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study explores the diversity of local cultures in implementing the curriculum in elementary schools in Banggai District, an area rich in distinctive and diverse local cultures. To maintain the noble values ​​of the Indonesian nation, this cultural diversity needs to be preserved and developed through education. One way to make this happen is through utilizing local culture in the curriculum structure, known as local content. This research uses a local cultural analysis approach in the development of the basic education curriculum, with the following stages: first, identification of the curriculum context, which includes an analysis of characteristics, potential, advantages, local wisdom, and regional needs/demands. Second, an analysis of local culture, which will be developed in the basic education curriculum, includes four clusters of local content covering socio-cultural-political, economic, environmental, and other local-specific dimensions. The results of the study indicate that several elementary schools in Banggai Regency have implemented local content subjects in accordance with Banggai Regent Regulation No. 56 of 2017 concerning Local Language Local Content Curriculum (Saluan & Balantak). Based on an analysis of the context and potential of local culture and aspects of basic education curriculum development, several local cultures can be developed, including developing tourist destinations, developing regional languages, developing regional skills and craft industries, and preserving regional arts and sports.